1988
DOI: 10.1111/j.1471-0528.1988.tb06480.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of uterine activity in spontaneous labour using a microcomputer

Abstract: A . A. CALDER Professor Correspondencc: Dr F. M. Fairlie 1015-1021. 'I'romans. P. M . , Sheen, hl. A . Kc Bcazley. J. M. (1982) Fcto-matcrnal survcillancc iii labour: a iicw approach with an on-liiic microcomputer. Hr J O h m Gynaecol nY, 102 I -1030.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 11 publications
1
9
1
Order By: Relevance
“…We feel that the 2 stages of labor are arbitrary subdivisions of a continuum which both have significant pressure effects onto the pelvic floor. This view is supported by reports showing that substantial forces from the presenting part of the fetus are exerted on to the pelvic floor during the whole labor process [9][10][11]. Subdividing this continuum into arbitrary labor stages restricts the sampling of data and may introduce spurious statistical calculations.…”
Section: Discussionsupporting
confidence: 50%
“…We feel that the 2 stages of labor are arbitrary subdivisions of a continuum which both have significant pressure effects onto the pelvic floor. This view is supported by reports showing that substantial forces from the presenting part of the fetus are exerted on to the pelvic floor during the whole labor process [9][10][11]. Subdividing this continuum into arbitrary labor stages restricts the sampling of data and may introduce spurious statistical calculations.…”
Section: Discussionsupporting
confidence: 50%
“…Other investigators have directly analyzed uterine activity with and without epidural analgesia and found that such analgesia did not influence uterine activity in the first stage of labor. However, there was a lower level of uterine contraction, frequency, and intensity in the second stage 39 . It was hypothesized that the observed decrease in uterine activity during the second stage may contribute to the increased operative vaginal delivery rate 40 .…”
Section: Uncertaintiesmentioning
confidence: 81%
“…We addressed this question in our study with interesting results. We have previously shown that the level of uterine activity in spontaneous labour is lower in multiparous women compared with nulliparous women [4]. It would appear that this difference is mainly due to a lower contraction rate in multiparous women.…”
Section: Discussionmentioning
confidence: 95%
“…This was introduced into the amniotic cavity immediatedly after amniotomy as described by STEER [12]. A computer was used to analyse changes in intrauterine pressure and quantify uterine activity as previously reported [4,9]. Each time maternal blood was sampled for prostaglandin metabolite levels, uterine activity was quantified for a period of 20 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation